Assessment of functional outcome of surgical management of proximal humerus fracture treated with PHILOS plate - Jagiasi, Jairam D.; Patel, Mihir R.; Daliya, Sagar G.; Bochare, Amol; Vora, Manan (International Journal of Research in Orthopaedics, 2018)
Background: Proximal humeral fractures were treated conservatively in the past and often had compromised functional results. With the advancement of surgical techniques, these fractures, especially displaced, are now more often managed operatively; to meet the needs of the patient, provide early rehabilitation and better functional outcome. The aim of this study was to assess the functional outcome of operative management of proximal humeral fractures with Philos plate fixation. Methods: In this prospective study, 30 patients aged 19-75 years (mean age 47.1 years) with fractures of the proximal humerus, including two-, three-, and four-part fractures, were treated by open reduction internal fixation with Philos plating. Patients’ functional outcomes were evaluated based on subjective (35 points) and objective (65 points) parameters, as per the constant scoring system. Results: Functional outcome based on the constant scoring system of the patient at 6 month follow-up were compared. Excellent results were seen in 12 patients (40%), 2 had very good results (6.66%), 9 patients were having good (30%) and 6 had fair (20%) functional outcome. One patient had poor functional results (3.33%). Avascular necrosis (AVN) of the humeral head was observed in one patients. Conclusions: Philos plate fixation for proximal humeral fractures provides good stable fixation with good functional outcome and is a feasible option.